A Giant Verrucous Carcinoma of the Penis Presenting with Urinary Sepsis and Angina - Michael Nomikos; Paschalis Barmpoutis; Eleni Papakonstantinou; Zacharias Chousianitis; Prodromos Ouzounoglou; Paraskevi Efstathiadou; Charilaos Katsifotis (Case Reports in Medicine)
Penile verrucous carcinoma also known as Buschke-Löwenstein tumor in the genital region is an uncommon variant of penile carcinoma exhibiting slow, expansive growth. We present a case of a 63-year-old male who presented with a giant purulent penile mass causing urinary sepsis and angina. Regional lymph nodes were clinically negative and staging with CT scans of thorax and abdomen did not show any signs of lymph node or distant metastases. After resuscitation, radical penectomy was performed and a perineal urethrostomy was created. Histological examination revealed a Buschke-Löwenstein tumor of the penis with no invasion of corpus cavernosum and urethra.